Kinerja Ketahanan Pangan Indonesia: Pembelajaran dari Penilaian dengan Kriteria Global dan Nasional - Tono; Ariani, Mewa; Suryana, Achmad (Analisis Kebijakan Pertanian, 2023)
Fulfilling food and nutrition for all is a priority policy for national development. This policy aligns with Sustainable Development Goal 2, No Hunger. Achieving this target is not easy because Indonesia has a large population with positive growth. On the other hand, climate change and the degradation of land and water resources are continuing. The Covid-19 pandemic and geopolitical tensions currently exacerbate these challenges. This study aims to analyze the performance of Indonesia's food security and formulate policy recommendations. The primary sources of data and information come from the publication of the Global Food Security Index (GFSI) 2021 and the Food Security Vulnerability Atlas (FSVA) 2021. The data are analyzed descriptively and qualitatively. Based on GFSI, in 2021, from 113 countries studied, Indonesia's food security was ranked 69th. At the national level, based on the FSVA, Indonesia has achieved food security nationally. However, 74 out of 514 districts/cities were still vulnerable to food insecurity. Efforts to accelerate the achievement of food and nutrition security need to be focused on dimensions that are considered to have weak performance and in areas that are vulnerable to food insecurity, namely food 1) consumption and safety and 2) natural resources and resilience. In line with that, it is necessary to accelerate the development of basic service infrastructure (health, education, and roads), especially in Eastern Indonesia, and empower the community to increase their income. Food policies must be integrated and synergized with national economic and health policies.